A preliminary ecological and human health risk assessment for organic contaminants in composted municipal solid waste generated in New South Wales, Australia. (December 2019) - Langdon, Kate A.; Chandra, Anand; Bowles, Karl; Symons, Andrew; Pablo, Fleur; Osborne, Keith
Highlights: Land application of composted municipal solid waste can divert waste from landfill. Reuse can also be a route of entry into the environment for contaminants. This study ranked contaminants based on human health and/or ecological risk. Contaminants of concern in the material were identified from the study. Outcomes can be used by regulators to ensure risks from this material are managed. Abstract: Land application of composted municipal solid waste (C-MSW) can divert waste from landfill but can also be a route of entry into the environment for contaminants. This study presents a preliminary human health and ecological risk assessment for organic contaminants in C-MSW generated in New South Wales, Australia, to identify and prioritise contaminants of concern. Following an initial screening assessment, terrestrial and aquatic risks were assessed by predicted soil and water concentrations, respectively. The assessment ranked contaminants as very high, high, medium or low priority. A qualitative review was then used to identify contaminants of concern, which included polybrominated diphenyl ethers, phthalates, bisphenol A and dibutyltin. Phenol was initially categorised as very high priority but due to its rapid degradation in soil, this is likely to be overly-conservative. The herbicides dicamba and MCPA were categorised as medium priority or higher but due to uncertainties in the data, these categories are also likely to be overly-conservative. A range of contaminants had concentrations below the screening criteria and were therefore considered low risk. Many contaminants were below the limit of reporting in all samples and were therefore not considered to be sufficiently distributed in the material to pose a risk. Some contaminants were detected in the material but could not be assessed as no criteria were available. The information from this study can be used by regulators when managing land application of C-MSW to ensure that the risks to human health and the environment are managed appropriately.